Malaysian political development in the era of Najib Razak - Mohamad Fairuz Mat Ali,; Mohammad Agus Yusoff, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This article utilises Huntington’s concept of political development to access the political development in Malaysia during the era of Najib Razak. Three main indices were used to measure political development, namely institutionalisation, mobilisation, and economic growth. The data for this article were obtained from primary sources through interviews with authoritative informants, as well as secondary sources from books, journals, official government reports and news portals. Findings revealed that in terms of political institutionalisation, Najib Razak failed in forming strong and efficient government institutions in the executive, legislative and judicial branches. This failure suggests that Malaysia’s political institutionalisation has been corrupted. In addition, it was discovered that the political mobilisation during this era was passive. This is because Najib controlled the freedom of the media and speech, as well as restricted the civil rights of the people. In terms of economic growth, no significant changes were observed over the previous government in terms of GDP, per capita income, and poverty reduction of the people due to abuse of power, 1MDB scandal, malpractice, and secretive governance. The political decay later led to the defeat of Barisan Nasional for the first time in Malaysia’s political history since its independence in 1957.